As novas marcas visuais à luz dos princípios do direito comercial - Cesário, Kone Prieto Furtunato (2016)
The purpose of this doctoral thesis is to establish how the principles of commercial law legitimate the protection of new visual trademarks. Thus, the author introduces the new visual trademarks as defined from a positive semantic concept of atypical distinctive signs, which suggest a potential renewal of the paradigms of the trademark system. To this effect, the study was divided into two parts: in the first part, such signs are presented from the standpoint of branding development in terms of their semiotic formation; of marketing; and of how such signs are handled in the Brazilian and other trademark legal systems. The second part undertakes an analysis of these signs on a systematic reasoning in order to assess how their derived ownership rights and their respective protection of new visual trademarks arise through the principles of commercial law, especially in the light of the principles of the free initiative and free competition, seen as the purposeful principles of the norms inherent to the trademark system, and which embody the basic drivers of the relationship between new trademarks and entrepreneurial and developmental business activities. Therefore, in this sense, this thesis is based on the concept of regulation of the ownership of such signs as a means of legal protection of private investment